Toward Improved Triadic Functioning: Exploring the Interactions and Adaptations of Coaches, Parents and Athletes in Professional Academy Soccer Through the Adversity of COVID-19 - Maurice, James; Devonport, Tracey J.; Knight, Camilla J. (Frontiers in Psychology, 2021)
On March 23rd, 2020, elite soccer academies in the UK closed in compliance with the government enforced lockdown intended to contain the COVID-19 pandemic. This forced parents, players, and coaches to reconsider how they interacted with, and supported, one another. The aims of the present study were (a) to explore the perceptions of players, parents, and coaches (i.e., the athletic triangle) regarding how they interacted and collaborated with one another during the COVID-19 pandemic to support wellbeing and performance, and; (b) to identify opportunities to enhance workings of those within the athletic triangle resulting from adaptions made following enforced lockdown. Using an interpretive description methodology, semi-structured interviews were conducted with five coaches, six players, and six parents from an English elite academy soccer club. Interviews were analysed using thematic analysis. Findings highlighted (a) the importance of support and the different means of communication used between members of the athletic triangle to facilitate such support; (b) the increased understanding of each member of the athletic triangle, leading to enhanced relationships, and; (c) how members of the athletic triangle adapted practice to facilitate relationship development during the pandemic and beyond. The identification of these considerations has implications for coach and parent education initiatives to allow for optimal functioning of the athletic triangle as elite academy soccer clubs return from lockdown. These include (a) the importance of continued communication between coach, athlete and parent; (b) increasing understanding of each individual within the athletic triangle; and (c) utilising key interpersonal and technological skills learnt during the lockdown to further facilitate engagement within the athletic triangle.